Correlation analysis of cytokines level and peripheral blood T lymphocyte subsets in systemic vascular inflammatory disease: Cytokines level and peripheral blood T lymphocyte subsets in systemic vascular inflammatory disease - Lin, Zhonghan; Dong, Xuanyang; Chen, Junye; Li, Biao (Journal of Medical Biochemistry, 2025)
Objective: To measure the levels of T-cell subsets and cytokines in the peripheral blood of patients with systemic vascular inflammatory disease and to analyze the influence of different clinical characteristics of systemic vascular inflammatory disease patients on the levels of T-cell subsets and cytokines in the peripheral blood. Methods: The case group consisted of 80 systemic vascular inflammatory disease patients who were diagnosed and treated at our hospital between January 2021 and December 2024. Forty healthy volunteers were selected from our hospital’s health assessment center to form the control group. The expression of helper T-cell (Th)1, Th17 and regulatory T-cell (Treg) subsets in the peripheral circulation was determined via flow cytometry. The levels of the cytokines interleukin and interferon-γ (IFN-γ) in the serum were measured via enzyme-linked immunosorbent assay (ELISA). levels of tumor necrosis factor-α (TNF-α), IL-4, IL-10, IL-17, and IL-6. Results: Compared with those in the control group, the expression levels of total T lymphoid subsets and CD8+ T and Th1 cells in systemic vascular inflammatory disease patients were significantly greater, and there was no statistically significant difference in Th, Th17, or Treg cell expression between the groups (P>0.05). However, there were statistically significant differences between the two groups [68.75 (54.23, 80.32)] and [72.10 (62.23, 86.45)], [23.44 (12.89, 33.76)] and [31.46 (20.13, 45.26)], [10.67 (8.23, 12.35)] and [10.26, 17.96 [25.39)], Z = -3.13, -4.54, -3.97 (all P values <0.05). Compared with those in the control group, systemic vascular inflammatory disease patients had significantly higher serum levels of IL-17, IL-6, TNF-α, IL-4, and IFN-γ, whereas their serum levels of IL-10 were significantly lower. The differences were statistically significant (Z = -4.32, -5.01, -8.18, -8.70, -3.48, and -8.30). The P values were all <0.05. Compared with that in patients without related manifestations, IL-6 expression was noticeably higher in systemic vascular inflammatory disease patients with arthritic symptoms and those with active systemic vascular inflammatory disease, and the difference was statistically significant pg/mL: [3.23 (2.98, 5.35)] compared with [10.51 (6.72, 23.21)], [6.32 (4.79, 8.93)] compared with [9.68 (6.97, 18.73)], Z = 5.47, 8.76, P values < 0.05. Compared with those in patients without relevant clinical manifestations, the levels of TNF-α in patients with arthritis manifestations, ocular manifestations, digestive tract manifestations and active systemic vascular inflammatory disease were significantly greater, whereas the levels of IFN-γ in systemic vascular inflammatory disease patients with digestive system lesions were significantly greater. The differences were statistically significant pg/mL: [7.74 (6.89, 10.19)] compared with [39.84 (30.37, 50.61)], [6.12 (5.36, 9.89)] compared with [31.35 (15.71, 30.46)], [6.49 (4.78, 10.21)] compared with [19.89 (14.36, 36.21)]. [5.89 (4.61, 8.96)] than [27.91 (15.32, 37.81)], [6.89 (5.43, 14.86)] than [26.79 (15.41, 31.56)], Z = 7.70, 6.84, 6.94, 9.47, 5.70, P values < 0.05. However, there was no statistically significant difference in the expression levels of IL-4 and IL-17 between systemic vascular inflammatory disease patients without relevant clinical manifestations and those with relevant clinical manifestations (P>0.05). Conclusion: Patients with systemic vascular inflammatory disease have an imbalance of T lymphocyte subsets and cytokines, and disease activity and clinical classification may involve an imbalance of T-cell subsets and cytokines.